2018
DOI: 10.3390/molecules23051045
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Drug Development of Carbonic Anhydrase Inhibitors beyond the Active Site

Abstract: Carbonic anhydrases (CAs) catalyze the reversible hydration of carbon dioxide to produce bicarbonate and a proton. Multiple CA isoforms are implicated in a range of diseases, including cancer. In solid tumors, continuously dividing cells create hypoxic conditions that eventually lead to an acidic microenvironment. Hypoxic tumor cells have different mechanisms in place to regulate and adjust the surrounding microenvironment for survival. These mechanisms include expression of CA isoform IX (CA IX) and XII (CA X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 118 publications
1
73
0
Order By: Relevance
“…Therefore, it was concluded that the structural effect had a more significant impact on the pK a . The deprotonated structure of (2) can be deduced from that of CA [42,43]. It can be deduced that the O atom of the hydroxyl substituent at position two of the pyridine unit and the H atom of the Zn-bound hydroxide ion form a hydrogen bond to stabilize the structure.…”
Section: Complexesmentioning
confidence: 99%
“…Therefore, it was concluded that the structural effect had a more significant impact on the pK a . The deprotonated structure of (2) can be deduced from that of CA [42,43]. It can be deduced that the O atom of the hydroxyl substituent at position two of the pyridine unit and the H atom of the Zn-bound hydroxide ion form a hydrogen bond to stabilize the structure.…”
Section: Complexesmentioning
confidence: 99%
“…Specific interference with tumor H + dynamics (pH i and pH e ) and/or upregulated glycolytic metabolism may be an important step towards reversing the disrupted pH gradient and better treatment of solid tumors [9,46]. This approach has been made in a number of pre-clinical and also clinical studies by buffer/bicarbonate therapy [47,48], targeting pH regulating transporters and carbonic anhydrases [49] and pH-sensitive drug delivery systems [46]. Among these, PPIs are supposedly in the most advanced stages of clinical trials for prostate, colorectal and esophageal cancer [46,50], and it is presumed that they interact with cysteines of V-ATPases and other lysosomal and plasma membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab, and others, have also hypothesized that CA IX serves to regulate pH e by responding to changes in substrate concentration (10,19,20). As pH e decreases, CA IX sequesters protons in the form of CO 2 and H 2 O through the dehydration reaction (27,32,33). As pH e increases CA IX produces HCO 3 and H + via the hydration reaction (27,33).…”
Section: Introductionmentioning
confidence: 93%